Quantitative characterization of recombinase-based digitizer circuits enables predictable amplification of biological signals - Katherine A. Kiwimagi; Justin H. Letendre; Benjamin H. Weinberg; Junmin Wang; Mingzhe Chen; Leandro Watanabe; Chris J. Myers; Jacob Beal; Wilson W. Wong; Ron Weiss (Communications Biology, 2021)
Kiwimagi & Letendre et al. present a workflow to quantitatively define recombinase-based digitizer and predict responses to different input signals. With a mechanistic/phenotypic model that can predict circuit performance, they generate a synthetic cell-cell communication device that amplifies a synNotch output signal.